2021
DOI: 10.3389/fpubh.2020.589966
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing: Prevalence of Depressive, Anxiety, and Stress Symptoms Among Brazilian Students During the COVID-19 Pandemic

Abstract: Social distancing due to the COVID-19 pandemic can impact mental health, triggering symptoms such as anxiety, stress and depression. Therefore, this study aimed to assess the levels of anxiety, depression and stress during the period of social distancing due to COVID-19 in students from a campus of the Federal Institute in the metropolitan area of Porto Alegre/RS. A correlational and exploratory study was performed. The sample of the present research was composed by 208 students, who responded to a self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 18 publications
3
40
0
2
Order By: Relevance
“…In terms of interventions, reducing COVID-19 concern may require efforts to promote active coping (see El-Monshed et al., 2021 ) and resilience ( Chmitorz et al., 2018 ; Steinhardt and Dolbier, 2008 ). Other interventions may aim to encourage physical exercise, preferably outdoors whenever possible, which is known to improve mood (see Esteves et al., 2021 ; Browning et al., 2021 ). Many of interventions can be administered through online and mobile platforms, including loneliness interventions among college students (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of interventions, reducing COVID-19 concern may require efforts to promote active coping (see El-Monshed et al., 2021 ) and resilience ( Chmitorz et al., 2018 ; Steinhardt and Dolbier, 2008 ). Other interventions may aim to encourage physical exercise, preferably outdoors whenever possible, which is known to improve mood (see Esteves et al., 2021 ; Browning et al., 2021 ). Many of interventions can be administered through online and mobile platforms, including loneliness interventions among college students (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with college students in two Brazilian cities showed a high prevalence of symptoms of stress, depression, anxiety, and mood swings. In addition, engagement in physical activity was associated with better psychological outcomes [31,32].…”
Section: Introductionmentioning
confidence: 98%
“…In this respect, Jones et al ( 2021 ), studying the City University of New York, underlined that more than half of the interviewed students (54.5%) reported relevant levels of anxiety/depression and an increased need for mental health services due to the pandemic. Esteves et al ( 2021 ) detected a positive association between high levels of anxiety symptoms and occurrence of sleep problems among Brazilian university students during the lockdown period. Garvey et al ( 2021 ), using the GAD-7 (7-items Generalized Anxiety Disorder scale) test to detect anxiety levels in Spain, found a relevant proportion of university students affected by high levels of anxiety connected to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Several analyses applied to university students showed higher rates of anxiety/depression and financial instability due to the pandemic all over the world (e.g., Esteves et al, 2021 ; Garvey et al, 2021 ; Jones et al, 2021 ). In this respect, Jones et al ( 2021 ), studying the City University of New York, underlined that more than half of the interviewed students (54.5%) reported relevant levels of anxiety/depression and an increased need for mental health services due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%